Blepharophimosis‐ptosis‐intellectual disability syndrome: A report of nine Egyptian patients with further expansion of phenotypic and mutational spectrum. Issue 12 (19th September 2020) - Zaki, Maha S.; Otaify, Ghada A.; Ismail, Samira; Issa, Mahmoud Y.; El‐Ruby, Mona O.; Sadek, Abdelrahim A.; Ashaat, Engy A.; El Saeidi, Sonia A.; Aglan, Mona S.; Temtamy, Samia; Abdel‐Hamid, Mohamed S.
Abstract: Blepharophimosis‐ptosis‐intellectual disability syndrome (BPID) is an extremely rare recognizable blepharophimosis intellectual disability syndrome (BID). It is caused by biallelic variants in the UBE3B gene with only 24 patients described worldwide. Herein, we report on the clinical, brain imaging and molecular findings of additional nine patients from six unrelated Egyptian families. Patients presented with the characteristic features of the syndrome including blepharophimosis, ptosis, upslanted palpebral fissures with epicanthic folds, hypertelorism, long philtrum, high arched palate, micrognathia, microcephaly, and intellectual disability. Other findings were congenital heart disease (5 patients), talipes equinovarus (5 patients), genital anomalies (5 patients), autistic features (4 patients), cleft palate (2 patients), hearing loss (2 patients), and renal anomalies (1 patient). New or rarely reported findings were spherophakia, subvalvular aortic stenosis and hypoplastic nails, and terminal phalanges. Brain MRI, performed for 7 patients, showed hypogenesis or almost complete agenesis of corpus callosum. Genetic studies revealed five novel homozygous UBE3B variants. Of them, the c.1076G>A (p.W359*) was found in three patients from two unrelated families who shared similar haplotype suggesting a likely founder effect. Our results strengthen the clinical, dysmorphic, and brain imaging characteristic of this unique type of BID and extend the mutational spectrum associated with the disorder.